Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793715
|View full text |Cite
|
Sign up to set email alerts
|

Learning Discriminative Embeddings for Object Recognition on-the-fly

Abstract: We address the problem of learning to recognize new objects on-the-fly efficiently. When using CNNs, a typical approach for learning new objects is by fine-tuning the model. However, this approach relies on the assumption that the original training set is available and requires high-end computational resources for training the ever-growing dataset efficiently, which can be unfeasible for robots with limited hardware. To overcome these limitations, we propose a new architecture that: 1) Instead of predicting la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Our work builds on the findings from [5] for learning to recognize objects on-the-fly. However, to make the scalable real-time recognition system that we are after, we propose the following contributions.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work builds on the findings from [5] for learning to recognize objects on-the-fly. However, to make the scalable real-time recognition system that we are after, we propose the following contributions.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…While [3], [4] were designed for domain adaptation between in-vitro and in-situ, they empirically demonstrated that a ConvNet can be used to learn new objects without having to retrain the model by performing the k-nearest neighbors search in the features space, where data points from the same object are close to each other and separated otherwise. [5] builds on the same idea of utilizing a discriminative ConvNet and simplifies the model into a single branch that uses a combination of Softmax and Triplet Loss for achieving stateof-the-art accuracy for learning objects on-the-fly. We follow this research direction of utilizing discriminative networks for learning new objects without the need for retraining, and therefore, we focus this literature review on supervised approaches that learn discriminative features by utilizing regularizers in the loss function.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…To train the network, we used the triplet loss algorithm. It is a well-established method that finds its uses in many areas, including image retrieval, object recognition, and biometric verification [22,29,30]. This approach especially lends itself to the problem of biometric verification, as there exist a considerable amount of classes (each person could be considered a separate class), and their total number is not known at the training time.…”
Section: Network Training Algorithmmentioning
confidence: 99%